The Differences Between Ghulām and Walad: The Stories of Zakariā and Maryam - Ghoniyah, Sofi; Abdillah, A. Mughzi (Universitas Negeri Malang, 2024)
Arabic is the Qur'anic language used by all Muslims to worship. Arabic is superior to other languages not only because it is the language of the Qur'an but Arabic has characteristics that make it unique compared to other languages worldwide. One of its uniqueness is the number of synonyms owned by one vocabulary. These synonyms are also found in the Qur'an with various interpretations. Synonyms are not merely different vocabulary and the same meaning, but each vocabulary with the same meaning has a unique meaning not owned by other vocabularies. This study aims to analyze the differences in the use of a child's vocabulary based on the context of the story contained in Surah Ali Imran verses 40 and 47 relating to the story of Prophet Zakariā and Maryam. In this study, the researcher used descriptive qualitative methods and documentation techniques. The result of this research is that ghulām and walad have differences in four aspects: the origin of creation, the process of being born, the relationship with parents, and the wishes of parents.